Persisting Effects of Ayahuasca on Empathy, Creative Thinking, Decentering, Personality, and Well-Being - Kiraga, Maggie K.; Mason, Natasha L.; Uthaug, Malin V.; van Oorsouw, Kim I.M.; Toennes, Stefan W.; Ramaekers, Johannes G.; Kuypers, Kim P. C. (Frontiers in Pharmacology, 2021)
Background Naturalistic and placebo-controlled studies have suggested that ayahuasca, a traditional Amazonian beverage, could be helpful in the treatment of psychopathologies like depression and anxiety disorders by changing otherwise disturbed cognitive and emotional processes. To better understand its full therapeutic potential, one way is to study the effects on processes like flexible thinking, empathy, and well-being, which are normally compromised in stress-related psychopathologies. Materials and Methods Volunteers attending ayahuasca ceremonies were asked to complete a test battery at three separate occasions: baseline, the morning after, and one week after the ceremony. We included the constructs of creative thinking (measured by Picture Concept Task), empathy (Multifaceted Empathy Test), satisfaction with life (Satisfaction with Life Scale), decentering (Experiences Questionnaire), and personality (Big Five Inventory) into the test battery. Additionally, the psychedelic experience was quantified with the Persisting Effects Questionnaire, the Ego Dissolution Scale, and Visual Analogue Scales. Results In total, 43 attendees (males= 22; females= 21) completed parts of the baseline assessment, 20 (males= 12; females= 8) completed assessments in the morning after the ceremony, and 19 (males= 14; females= 5) completed assessments at the one-week follow-up. At one and seven days post-ceremony, cognitive empathy, satisfaction with life, and decentering increased, while divergent thinking (Fluency corrected for Originality) decreased, when compared to baseline. Implicit emotional empathy increased at one-week follow-up, whereas ratings of the trait neuroticism decreased. Conclusion The study suggests that a single ingestion of ayahuasca in a social setting is associated with enhancement of subjective well-being, an enhanced ability to take an objective and non-judging stance towards the self (decentering), and the ability to correctly recognize emotions in others, compared to baseline, lasting up to one week post-ceremony. To understand the therapeutic potential related to these effects, further research with clinical populations is needed in which these effects can be assessed, including its link with therapeutic outcomes. Together, this will increase our understanding of the effectiveness and breadth of future therapeutic options.